Television viewing habits and school performance of grade 1 pupils - De Ocampo, Mary Antonette C. (2007)
This correlational research was conducted among Grade I pupils of the UP Integrated School (UPIS). It examined the relationship between television viewing habits and the grade one pupils of the UPIS performance through the General Weighted Average in one year. It assessed how parental involvement contributed to the television viewing habits of the child. The TV viewing habits were assessed by a survey instrument together with the pupil's profile, their parents and parental involvement together with a questionnaire. The study showed no significant difference between the relationship of the television viewing habits as to whether they contributed to the pupil's school performance. The results of this study may aid educational technologists to come up with a comprehensive approach to media pedagogy, to ascertain how TV can influence the education of the youth.